Big House, Little House, Back House, Barn : The Connected Farm Buildings of New England - Hubka, Thomas C., 1946- (Book collections on Project MUSE., 2022)
A classic work on farm buildings made by nineteenth-century New Englanders refreshed with a new introduction. Big House, Little House, Back House, Barn portrays the four essential components of the stately and beautiful connected farm buildings made by nineteenth-century New Englanders that stand today as a living expression of a rural culture, offering insights into the people who made them and their agricultural way of life. A visual delight as well as an engaging tribute to our nineteenth-century forebears, this book, first published nearly forty years ago, has become one of the standard works on regional farmsteads in America. This new edition features a new preface by the author.